La crítica : artes, medios y tendencias - Rincón, Omar; Carrión, Jorge (Colección Séneca., 2016)
"This book is an exercise of teachers from the Faculty of Arts and Humanities of the Universidad de los Andes in Bogotá (Colombia), on how to do criticism and in what is the task of understanding and explaining the arts and cultures of our time. We are not a collective; each explores their own field and provide criteria to exercise criticism. We avoid purities, the solemn, virtuous, since we are interested in the culture inserted in this world and that takes forms of decadence. For this reason, we understand criticism as this exciting practice of thinking freely without moralizing anyone." (Our translation)--Verso Cover.